The PERBANDINGAN IMPLEMENTASI OTONOMI KHUSUS: STUDI KASUS CAPAIAN PEMBANGUNAN EKONOMI DAN SOSIAL DI PROVINSI ACEH DAN PAPUA: PENDAHULUAN, TINJAUAN PUSTAKA, METODE PENELITIAN, HASIL PENELITIAN DAN PEMBAHASAN, KESIMPULAN DAN SARAN, DAFTAR PUSTAKA - putri sulastri (JARUM: Journal of Analysis Research and Management Review, 2026)
This study examines the comparison of special autonomy implementation in Aceh and Papua with a focus on development outcomes. The main question addressed is why the same policy produces different results in the two provinces and what problems arise in its implementation. The study uses a qualitative method with a literature study approach by collecting data from scientific journals, books, and official documents related to special autonomy policies. The analysis is conducted by comparing findings from various sources to identify patterns, similarities, and differences in implementation and outcomes. The results show that Aceh demonstrates relatively better performance due to political stability, the presence of local political institutions, and more structured fund management. In contrast, Papua continues to face significant challenges such as development inequality, limited institutional capacity, low public trust, and less effective fund utilization. Special autonomy funds contribute positively to regional economic growth, but their impact on social welfare remains uneven. In Aceh, improvements are more visible in the education sector, while in Papua the socio-economic impact is still moderate and not sufficient to reduce disparities significantly. The findings indicate that the effectiveness of special autonomy is not solely determined by the amount of funds allocated, but also by governance quality, institutional capacity, and local conditions. In conclusion, Aceh shows higher development achievement under special autonomy, while Papua still encounters substantial barriers that hinder the realization of policy goals. This study contributes to the existing literature by providing a comparative analysis that highlights how governance and local conditions shape the effectiveness of special autonomy policies.